Vitamin D Replacement Mitigates Menopause-Associated Dyslipidaemia and Atherogenic Indices in Ovariectomized Rats; A Biochemical Study - Muhammad, Marwa Hassan; Hussien, Noha Ibrahim; Elwia, Sania K. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background & Aim Dyslipidaemia is highly prevalent among postmenopausal women and its management represents a keystone in the prevention of the worldwide increase in cardiovascular morbidity and mortality. Therapy choices for menopause-associated dyslipidaemia are limited and a matter of debate. So, it becomes prudent to search for natural safe alternatives. Vitamin D (VD) has been acknowledged as an essential factor in cardiovascular health. Thus, we aimed to illustrate the impact of different VD status on dyslipidaemia and atherogenic indices.Method 5 groups of rats were conducted; SHAM group fed control diet, ovariectomized rats fed control diet (OVX), ovariectomized rats fed VD-sufficient-high fat diet (HFD) (1 000 IU/ kg diet), ovariectomized rats fed VD-deficient-HFD (25 IU/ kg diet), and ovariectomized rats fed VD-replete-HFD (10 000 IU/ kg diet) for 16 weeks.Results Dyslipidaemia with an increased atherogenic index of plasma, atherosclerosis coefficient, cardiac risk ratio, and aortic total cholesterol accumulation in addition to reduced serum 25-hydroxy-VD levels was observed in the OVX and VD-sufficient HFD versus SHAM. These findings were aggravated by VD-deficient-HFD while reversed by VD-replete-HFD. The VD-mediated abundance of aortic ATP-binding cassette transporter A1 (ABCA1) expression, reduced activity of the inflammatory Jun N-terminal kinases (JNK), and downregulation of aortic cluster of differentiation-36 (CD36) receptors expression together with increased serum total antioxidant capacity and reduced serum malondialdehyde were among the supposed mechanisms.Conclusions Our study sheds light on alarming levels of VD deficiency among ovariectomized rats. VD repletion improved the menopause-associated dyslipidaemia and atherogenic indices through hypolipidemic, antioxidant, and anti-inflammatory effects.
Keywords: Ovariectomized rats; vitamin D status; dyslipidaemia; atherogenic indices; ABCA1/JNK/CD36